Kajian Kritis Pembentukan Pemerintahan Kampung Adat di Kabupaten Siak - Haryono, Dodi (Magister (S2) Ilmu Hukum Fakultas Hukum Universitas Riau, 2017)
AbstractÂ The purpose of this research is to know the implementation of the formation of customary village governance based on Siak District Regulation No 2 of 2015 on Stipulation of customary village in Siak District, following the obstacles and efforts made to overcome obstacles in the implemetation of the formation of customary village. Based on Law No 6 of 2014 on Villages, Siak District Government has established Siak District Regulation No 2 of 2015 on Stipulation of customary village in Siak District which is a typical local government system based on the right of origin and traditional rights of society in Siak District. Although in its formation has been in accordance with the prevailing regulation, but in its formation is still found weaknesses that affect the effectiveness on the implementation of this regulation, so it needs improvement efforts for better governance of customery village.Â AbstrakÂ Tujuan penulisan ini ialah mengetahui pelaksanaan pembentukan Pemerintahan Kampung Adat berdasarkan Peraturan Daerah Kabupaten Siak Nomor 2 Tahun 2015 tentang Penetapan Kampung Adat Di Kabupaten Siak, berikut hambatan serta upaya yang dilakukan untuk mengatasi hambatan dalam pelaksanaan pembentukan Pemerintahan Kampung Adat. Berdasarkan Undang-Undang Nomor 6 Tahun 2014 tentang Desa, Pemerintah Kabupaten Siak telah membentuk Peraturan Daerah Kabupaten Siak Nomor 2 Tahun 2015 tentang Penetapan Kampung Adat di Kabupaten Siak yang merupakan sistem pemerintahan lokal yang khas berdasarkan hak asal usul dan hak tradisional masyarakat di Kabupaten Siak. Meskipun dalam pembentukannya telah sesuai dengan peraturan perundang-undangan yang berlaku, namun ditemukan kelemahan yang mempengaruhi efektivitas pelaksanaan Peraturan Daerah ini, sehingga diperlukan upaya perbaikan guna penataan Pemerintahan Kampung Adat yang lebih baik.